The Natural Gas Consumption and Economic Development Nexus: Fresh Evidence from Indonesia - Bulkani, Bulkani; Sonedi, Sonedi; Putra, Chandra Anugrah (International Journal of Energy Economics and Policy, 2020)
Indonesia is the 26th largest natural gas consuming country in the world. Currently the government is strategically planning to get into developed countries by boosting up the status of its economic growth. This study empirically examines the situation of country’s strategic planning to get achieved by utilizing the available resources and the association between capital and labor, natural-gas (NG) consumptions, and exports of the country. The current study is utilizing time-series data from the year 1980 to 2018. In order to confirm the cointegration Johansen Cointegration technique has been used while short-run and long-run coefficients are estimated by applying ARDL bound test. Results indicate that economic growth reduces while exports, and the consumption of capital and labor boost the use of natural gas (NG) in Indonesia. So, an affiliation between consuming natural gas consumption effects inversely by the economic growth of Indonesia. Furthermore, labor utilization plays a significant and maximum contribution in the consumption of NG and also in the GDP of the country. This research recommends the active manipulation of natural gas availability and resources of Indonesia, a strenuous determination in order to develop labor resources and protection a representative time in planning amongst other resources. Keywords: Natural Gas, Economic Growth, Capital, Labor, Johansen Cointegration, ARDL JEL Classifications: O13, Q42, Q43 DOI: https://doi.org/10.32479/ijeep.10781